Contribution to the knowledge of the African entomical biodiversity. I. – Pericordus goergeni n. sp. from the Republic of Benin (Coleoptera, Brentidae, Eremoxenini) - (:unkn) unknown (My University, 2015)
Pericordus goergeni n. sp. (Brentidae, Eremoxenini) is described from the Republic of Benin. It is easily distinguished from the five Pericordus known to date, all in Africa, by the absence of métarostral bridge, replaced by a deep transverse depression.
Keywords: African Research